Advances in genetic improvement for salmon and trout aquaculture: the Chilean situation and prospects. (25th April 2019) - Lhorente, Jean P.; Araneda, Marcelo; Neira, Roberto; Yáñez, José M.
Abstract: Genetic improvement is key to the development of a more efficient aquaculture industry. By 2010, there were 104 breeding programmes for aquaculture species in the world, most of them for fish species. Usually, the breeding goals include traits such as growth rate, disease resistance, maturation and carcass quality. Resistance to specific pathogens has been one of the main objectives of research and development in the genetic improvement programmes of salmonids in Chile and worldwide. In Chile, trait selection has been conducted through the application of selection indexes. New technologies like next generation sequencing and genotyping have helped disentangle the genetic basis and enhance genetic evaluation methods of economically important traits. This work aims to review the advances in genetic improvement for salmon and trout aquaculture with emphasis on the Chilean experience. We focus on the implementation of breeding programmes in the country, definition of breeding objectives, results on genetic parameters and response to selection and incorporation of genomics. Future challenges and opportunities regarding genotype‐by‐environment interactions, climate change and research and development, plus the demonstration of the economic benefit of breeding programmes are also addressed.